Efficacy of disinfection procedures to reduce Acinetobacter baumanii blaOXA-23 contamination rate of needleless connectors: an in-vitro study - C. Biazus-Dalcin; T.C.M. Sincero; C.P. Zamparette; D.C. Tartari; S. de Souza; T.L. Silva; A. Tomazoni; P.K. Rocha (Elsevier, 2024)
Summary: Aim: This study aimed to verify the efficacy of disinfection procedures to reduce Acinetobacter baumannii blaOXA-23 bacterial load in needleless connectors that had been experimentally contaminated. Methods: Two-way intermediate extender's hub and needle-free valve were contaminated with Acinetobacter baumannii blaOXA-23. To disinfect them, the following procedures were carried out: sterile gauze with 70% ethanol, sterile gauze with Incidin®, and 70% isopropyl alcohol single-use cap, with eight times friction for 10 s, followed by 5 s drying time. The statistical tests Kruskal-Wallis and post-hoc Conover were performed using MedCalc®. Results: A total of 82 experiments were conducted. All tested disinfection procedures were efficacious in reducing the A. baumannii blaOXA-23 load. The 70% IPA single-use cap was found to be the best method for disinfecting the two-way intermediate extender's hub (87.28%), while all the methods were efficacious for the disinfection of the needle-free valve (more than 90%). During the inoculation period, A. baumannii blaOXA-23 showed less adherence to the needle-free valve during the inoculation period, probably due to the device's design. Conclusion: The three tested disinfection procedures using sterile gauze with 70% ethanol, sterile gauze with Incidin®, and 70% IPA single-use cap were found to be efficacious in reducing the bacterial load of A. baumanni blaOXA-23 in needleless connectors. Proper disinfection of needleless connectors is a crucial nursing practice to prevent bloodstream infections, as it significantly reduces the bacterial load present in the device.